2010
DOI: 10.1111/j.1469-8137.2009.03176.x
|View full text |Cite
|
Sign up to set email alerts
|

Silica uptake in aquatic and wetland macrophytes: a strategic choice between silica, lignin and cellulose?

Abstract: *Although silica (Si) is not an essential element for plant growth in the classical sense, evidence points towards its functionality for a better resistance against (a)biotic stress. Recently, it was shown that wetland vegetation has a considerable impact on silica biogeochemistry. However, detailed information on Si uptake in aquatic macrophytes is lacking. *We investigated the biogenic silica (BSi), cellulose and lignin content of 16 aquatic/wetland species along the Biebrza river (Poland) in June 2006 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
161
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 208 publications
(182 citation statements)
references
References 38 publications
13
161
2
1
Order By: Relevance
“…This idea is supported by a comparison study of multiple physical defenses of plants in natural habitats that found higher levels of silica were sometimes associated with higher levels of lignin and cellulose (Schoelynck et al 2010). However, under controlled environmental conditions we found no difference in lignin and less, not more, cellulose in Si+ than Si-plants.…”
Section: Discussionsupporting
confidence: 54%
“…This idea is supported by a comparison study of multiple physical defenses of plants in natural habitats that found higher levels of silica were sometimes associated with higher levels of lignin and cellulose (Schoelynck et al 2010). However, under controlled environmental conditions we found no difference in lignin and less, not more, cellulose in Si+ than Si-plants.…”
Section: Discussionsupporting
confidence: 54%
“…Hackney et al (2000) indicated that high diatom production in tidal marshes and the food web dependent on this production could actually be important contributors to estuarine production (as earlier suggested by Sullivan and Moncreiff 1990). Macrophytes are another factor in autochthonous production of BSi; aquatic and wetland plants can contain significant amounts of BSi (Schoelynck et al 2010). In freshwater marshes, Phragmites australis is particularly rich in BSi (Struyf et al 2007b; up to 5% of the dry biomass in dead reed culms is BSi in saltwater and mesohaline marshes, the dry biomass of Spartina alterniflora and Juncus roemerianus contains up to ±0.5% of BSi (Norris and Hackney 1999;Querné et al 2012).…”
Section: Fluxes Of Silicamentioning
confidence: 97%
“…The plants need to find a balance between cellulose, lignin and Si incorporation to be rigid but still flexible. Thus, it could be assumed that aquatic macrophyte Si metabolism is closely linked with cellulose and lignin metabolism (Schoelynck et al, 2010).…”
Section: Silicamentioning
confidence: 99%